Analysis of Earnings From Household Enterprises: Methodology and Application to Thailand - Chiswick, Carmel U. (The Review of Economics and Statistics, 1983)
Burkhauser, Richard V., and Joseph F. Quinn, Is Mandatory Overrated? Evidence from the 1970s, Journal of Human Resources 18 (Summer 1983), 337-358. Irelan, Lola, Retirement History Study: Introduction, Social Security Bulletin (Nov. 1972), 3-8. Kotlikoff, Lawrence J., Testing the Theory of Social Security and Life-Cycle Accumulation, American Economic Review 69 (June 1979), 396-410. Kotlikoff, Lawrence J., Avia Spivak, and Lawrence H. Summers, Adequacy of Savings, American Economic Review 72 (Dec. 1982), 1056-1069. Quinn, Joseph, The Importance of Social Security and Pension Rights in Wealth Portfolios of Older Americans, presented at International Association for Research on Income and Wealth Conference, Gouvieux, France, August 16-23, 1981. Smeeding, Timothy, Approaches to Measuring and Valuing In-kind Subsidies and the Distribution of Their Benefits, in M. Moon (ed.), Social Accounting for Transfers, NBER Studies in Income and Wealth, vol. 48 (Chicago: University of Chicago Press, in press). U.S. Department of Health and Human Services, Social Security Bulletin Annual Statistical Supplement 1981 (Washington, D.C.: U.S. Government Printing Office, 1981). Weisbrod, Burton A., and W. Lee Hansen, An Income NetWorth Approach to Measuring Economic Welfare, American Economic Review 58 (Dec. 1968), 1315-1329. sented at International Associat on for Research on